The Endoplasmic Reticulum Unfolded Protein Response in Neurodegenerative Disorders and Its Potential Therapeutic Significance - Remondelli, Paolo; Renna, Maurizio (Frontiers in Molecular Neuroscience, 2017)
In eukaryotic cells, the endoplasmic reticulum (ER) is the cell compartment involved in secretory protein translocation and quality control of secretory protein folding. Different conditions can alter ER function, resulting in the accumulation of unfolded or misfolded proteins within the ER lumen. Such a condition, known as ER stress, elicits an integrated adaptive response known as the unfolded protein response (UPR) that aims to restore proteostasis within the secretory pathway. Conversely, in prolonged cell stress or insufficient adaptive response, UPR signalling causes cell death. ER dysfunctions are involved and contribute to neuronal degeneration in several human diseases, including Alzheimer, Parkinson and Huntington disease and amyotrophic lateral sclerosis. The correlations between ER stress and its signal transduction pathway known as the UPR with neuropathological changes are well established. In addition, much evidence suggests that genetic or pharmacological modulation of UPR could represent an effective strategy for minimising the progressive neuronal loss in neurodegenerative diseases. Here, we review recent results describing the main cellular mechanisms linking ER stress and UPR to neurodegeneration. Furthermore, we provide an up-to-date panoramic view of the currently pursued strategies for ameliorating the toxic effects of protein unfolding in disease by targeting the ER UPR pathway.